2016
DOI: 10.1039/c6ra08313g
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Listeria innocua on roll-to-roll produced SERS substrates with gold nanoparticles

Abstract: The rapid and accurate detection of food pathogens plays a critical role in the early prevention of foodborne epidemics.Current bacteria identification practises, including colony counting, polymerase chain reaction (PCR) and immunological methods, are time consuming and labour intensive; they are not ideal for achieving the required immediate diagnosis. Different SERS substrates have been studied for the detection of foodborne microbes. The majority of the approaches are either based on costly patterning tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 56 publications
1
25
0
1
Order By: Relevance
“…Furthermore, using methods of ultrashort laser ablation or fragmentation , one can prepare extremely stable aqueous solutions of “bare” (ligand‐free) Au NPs having unique surface chemistry and different reactivity compared to conventional colloidal nanomaterials. The absence of ligands and contaminants on the surface of such Au‐based NPs gives a promise for their successful use as mobile probes for SERS applications and their efficiency in such tasks was recently confirmed in our studies . Moreover, despite the absence of any biopolymer coating such “bare” Au NPs were found to have relatively low toxicity and a good cell uptake, which promises their successful use in live systems .…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, using methods of ultrashort laser ablation or fragmentation , one can prepare extremely stable aqueous solutions of “bare” (ligand‐free) Au NPs having unique surface chemistry and different reactivity compared to conventional colloidal nanomaterials. The absence of ligands and contaminants on the surface of such Au‐based NPs gives a promise for their successful use as mobile probes for SERS applications and their efficiency in such tasks was recently confirmed in our studies . Moreover, despite the absence of any biopolymer coating such “bare” Au NPs were found to have relatively low toxicity and a good cell uptake, which promises their successful use in live systems .…”
Section: Introductionsupporting
confidence: 69%
“…The beads were concentrated, the supernatant was removed and the captured bacteria with beads were resuspended into 100 mL of washing buffer for the SERS detection. The blank Raman spectrum of immunomagnetic separation (IMS) beads in LEE Broth can be found in our earlier study . Bacteria spectra were detected with 785 nm laser excitation, 60 seconds integration time, 50× objective and 7.5 mW power.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to measurements, the stock solution was centrifuged (CT15RE from VWR, Radnor, PA) at 4,000 rpm/1,610 g for 4 min, subsequently followed by a removal of the supernatant to reach a final concentration of about 2.8 g·L −1 . The effect of different size, shape and enhancement material was tested in our earlier studies, in which these Ag NPs showed good performance at different wavelengths with different spectroscopic set‐ups . The nanotoxicity of Ag NPs on E. coli cells was described elsewhere, which should not be relevant, as the assay was exclusively used during measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of different size, shape and enhancement material was tested in our earlier studies, in which these Ag NPs showed good performance at different wavelengths with different spectroscopic set-ups. 24,25 The nanotoxicity of Ag NPs on E. coli cells was described elsewhere, 26 which should not be relevant, as the assay was exclusively used during measurements.…”
Section: Chemicalsmentioning
confidence: 99%
“…Molecular biology methods, such as nucleic acid probe and gene chip, have high sensitivity, but need expensive equipment and skilled operation (Feng et al ., ; Skerniškyt≐ et al ., ). Various types of immunological detection methods like enzyme‐linked immunosorbent assay [(ELISA) Mendonça et al ., ; Mizutani et al ., ;], colloidal gold immunochromatography (Shan et al ., ) and immunomagnetic separation (IMS) method (Uusitalo et al ., ) have widely been used in pathogens and toxins detection. Among all immunological methods, immunochromatography is the simplest and quickest way to detect the pathogen in a sample within 15 min (Shim et al ., ).…”
Section: Introductionmentioning
confidence: 99%